BIBLIOMETRIC ANALYSIS OF ISLAMIC MICROFINANCE AND ITS CONTRIBUTION TO SUSTAINABLE DEVELOPMENT GOAL 8 - Maghfiro, Naura; Pratikto , M. Iqbal Surya (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
This study aims to analyze the development of research on Islamic microfinance and its contribution to the achievement of Sustainable Development Goal (SDG) 8: Decent Work and Economic Growth through a bibliometric approach. Data were collected from the Scopus database covering the publication period from 2010 to 2025 and analyzed using VOSviewer software to map publication trends, author collaboration, country distribution, and keyword co-occurrence. The results show a significant increase in research since 2015, peaking in 2024, with journal articles dominating 88.8% of publications. Indonesia and Malaysia are identified as the most productive countries, while research remains limited in Africa, Central Asia, and Europe. The analysis of keyword networks reveals a dominant focus on Islamic finance, financial inclusion, and economic growth, indicating that studies directly addressing SDG 8 indicators such as decent work and productivity growth are still scarce. Furthermore, author collaboration is relatively weak and concentrated regionally, reflecting the need to strengthen global research networks. These findings highlight important opportunities for future studies to expand empirical investigations, enhance cross-country collaboration, and integrate SDG 8 quantitative indicators to better understand the real contribution of Islamic microfinance to sustainable economic growth.